Hospital Cash Flow Management Strategies in Facing the Post-COVID-19 Global Health Crisis - Arrasily, Nailul Fithri; Minarsih, Try Jenny; Hartono, Budi; Daud, Alfani Ghutsa (Jurnal Ilmiah Ekotrans & Erudisi, 2025)
The COVID-19 pandemic has exposed significant vulnerabilities in global healthcare systems, severely impacting the financial and operational stability of hospitals. This systematic literature review analyzes the post-COVID-19 global health crisis's effects on hospital cash flow, identifies core principles of effective cash flow management, and formulates comprehensive strategies to enhance hospitals’ financial and operational resilience. This study employs the Systematic Literature Review (SLR) method as the primary approach to identify, evaluate, and synthesize findings from various sources of literature relevant to the research topic. Findings reveal that hospitals have faced sharp revenue declines and increased operational burdens, further exacerbated by challenges in claims processing and reimbursement systems. Nevertheless, adaptive hospitals demonstrated resilience through revenue diversification and cost efficiency. This report highlights the importance of proactive cash flow planning and monitoring, optimization of receivables and claims management, prudent debt management, operational efficiency, and strategic investment in digital transformation. Furthermore, human resource development and the establishment of strong crisis management teams are critical elements in building long-term resilience. Recommendations include adopting integrated technologies, enhancing collaboration, and advocating for more efficient payment systems to ensure the sustainability of healthcare services amid future global uncertainties.